Composite Bioinks With Mesoporous Bioactive Glasses—A Critical Evaluation of Results Obtained by In Vitro Experiments - Guduric, Vera; Wieckhusen, Johannes; Bernhardt, Anne; Ahlfeld, Tilman; Lode, Anja; Wu, Chengtie; Gelinsky, Michael (Frontiers in Bioengineering and Biotechnology, 2022)
Besides osteoconductivity and high degradation rate, mesoporous bioactive glasses (MBG) are specific for their highly ordered channel structure and high specific surface area, making them suitable as drug and/or growth factor delivery systems. On the other side, mesoporous channel structure, but also the MBG composition can have an effect on common cell evaluation assays, leading to inconclusive results. This effect is especially important when MBG is mixed in composite bioinks, together with cells. Additionally, the hydrogel component of the ink can influence the degradation of the MBG, leading to different ion release, which can additionally affect the analyses. Hence, our aim here was to show how MBG structure and composition influence common cell viability and differentiation assays when calcium (Ca) or magnesium (Mg)-containing glass is part of an alginate-based composite bioink. We suggested pre-labelling of cells with DiI prior to bioprinting and staining with Calcein AM, to allow identification of metabolically active cells expressing signals in both, green and red channel, allowing the use of fluorescence imaging for cell viability evaluations in the presence of high amounts (7 wt%) of MBG. The release and uptake of ions during degradation of CaMBG and MgMBG was significantly changed by alginate in the composite bioinks, as confirmed by higher release and uptake from bulk glasses. Additionally, we detected a burst release of Mg2+ from composites only after 24h of incubation. Furthermore, we demonstrated that released ions, but also the mesoporous channel structure, affect the measurement of lactate dehydrogenase (LDH) and alkaline phosphatase activity (ALP) in bioprinted composite scaffolds. Measured LDH activity was significantly decreased in the presence of CaMBG. On the other hand, presence of MgMBG induced increased signal measured for the ALP. Taken together, our findings show how composite bioinks containing MBG can interfere with common analyses, obtaining misleading results.